PROFIL KELAHIRAN BAYI PREMATUR DI RSUD DR. SOEBANDI JEMBER PERIODE 1 JANUARI 2003 â 31 DESEMBER 2005 - Kusuma, Irawan Fajar (FKM - UNEJ, 2009)
The premature delivery is one of the main risk factors of low birth weight and perinatal mortality. In Indonesia, the incidence of premature delivery is 10% whereas it is just 4% in the developed countries. The mortality rate caused by low birth weight is increasing from 6.8 per 1000 in 2001 to 7 per 1000 in a year period.Â Nowadays, the effort to reduce the perinatal mortality rate is still counting on neonatal intensive care which has highly cost. The aim of this study is to know profoundly about the attributes of premature deliveries at RSUD Dr Soebandi Jember between January 1st , 2003 and December 31st, 2005. The data were mainly obtained from the medical records of obstetry and ginaecology ward and 168 premature deliveries were included in this study. The result showed that among 168 premature deliveries, 75% of deliveries was conducted on indication. Factors that induced premature deliveries are placental dislocation, gestational hipertention, sistemic disturbance, pelvic head disproportion, and gemelli. The premature deliveries on gestational age were G1 / primigravida (43%), G2 (30%), G3 (11%), G4 (8%) and G5 or more (9%). The highest frequency of premature deliveries was on 20 - 35 year old women (70%). The most APGAR score of premature deliveries was 0 -3 (severe respiratory distress). Finally, the premature deliveries tend to be commonplace at woman with primigravida, 20-35 year old women and the outcome of them is generally worse to the baby. Keyword: premature deliveries, low birth weight, perinatal mortality